2017
DOI: 10.3847/1538-4357/835/2/205
|View full text |Cite
|
Sign up to set email alerts
|

Chasing Shadows: Rotation of the Azimuthal Asymmetry in the TW Hya Disk*

Abstract: We have obtained new images of the protoplanetary disk orbiting TW Hya in visible, total intensity light with the Space Telescope Imaging Spectrograph (STIS) on the Hubble Space Telescope (HST), using the newly commissioned BAR5 occulter. These HST/STIS observations achieved an inner working angle of ∼0 2, or 11.7 au, probing the system at angular radii coincident with recent images of the disk obtained by ALMA and in polarized intensity near-infrared light. By comparing our new STIS images to those taken with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
140
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(155 citation statements)
references
References 37 publications
14
140
1
Order By: Relevance
“…This hinted toward significantly misaligned inner disc components and/or the need for other dipper mechanisms. Evidence of misaligned inner discs has also been recently inferred for several systems using high-contrast optical/infrared images, which have revealed shadows in the outer disc cast by unseen inclined inner disc components (e.g., Marino et al 2015;Stolker et al 2016;Debes et al 2017; Benisty et al 2018;Casassus et al 2018). A notable example is the dipper J1604, which hosts a face-on transition disc resolved by ALMA (Ansdell et al 2016a) and variable shadows seen by VLT/SPHERE (Pinilla et al 2018a), suggesting a highly misaligned (∼70-90 • ) and dynamic inner disc component.…”
Section: Introductionmentioning
confidence: 83%
“…This hinted toward significantly misaligned inner disc components and/or the need for other dipper mechanisms. Evidence of misaligned inner discs has also been recently inferred for several systems using high-contrast optical/infrared images, which have revealed shadows in the outer disc cast by unseen inclined inner disc components (e.g., Marino et al 2015;Stolker et al 2016;Debes et al 2017; Benisty et al 2018;Casassus et al 2018). A notable example is the dipper J1604, which hosts a face-on transition disc resolved by ALMA (Ansdell et al 2016a) and variable shadows seen by VLT/SPHERE (Pinilla et al 2018a), suggesting a highly misaligned (∼70-90 • ) and dynamic inner disc component.…”
Section: Introductionmentioning
confidence: 83%
“…• 5 separations among adjacent images, thus obtaining a total field rotation of 120. • During data reduction, we reduce the impact from STIS' diffraction spikes and the BAR5 occulter using a mask created by Debes et al (2017). For a specific application to a groundbased dataset, see Section 4.2.…”
Section: Data Reductionmentioning
confidence: 99%
“…Several works have also suggested that the inner few AU of the TW Hya disk may either be warped or feature deviations from Keplerian rotation (e.g. Roberge et al 2005;Rosenfeld et al 2012;Debes et al 2017). These effects alone cannot create the axisymmetric substructures observed in the main CO isotopologues, but they would be worth considering in a more detailed analysis of the disk vertical structure.…”
Section: Comparison To Other Sourcesmentioning
confidence: 99%